Influencing shopper decisions : unleash the power of your brand to win customers - Brooks, Rebecca; Rogers, Devora (London : Kogan Page, 2022)
Constant change, rapid innovation, category disruptors, rising shopper expectations and new access to goods and services have made consumers and shoppers incredibly adept at wading through oceans of research and information. Before making a purchase decision, your brand's target consumer is a shopper. With more choices than ever before, shoppers are becoming increasingly promiscuous, opening themselves up to new brands, products and shopping channels. In Influencing Shopper Decisions, the authors are market researchers who reveal how brands can help shoppers say "yes" by better understanding consumer decision-making.
Includes bibliographic references and index.
Keywords: Branding (Marketing); Marketing; Advertising; Marketing; Marketing; marketing; Advertising; Marketing